2016
DOI: 10.1016/j.molbiopara.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach towards Trypanosoma brucei functional genomics using Gibson assembly

Abstract: Trypanosoma brucei is the causative agent of human African trypanosomiasis and nagana in cattle. Recent advances in high throughput phenotypic and interaction screens have identified a wealth of novel candidate proteins for diverse functions such as drug resistance, life cycle progression, and cytoskeletal biogenesis. Characterization of these proteins will allow a more mechanistic understanding of the biology of this important pathogen and could identify novel drug targets. However, methods for rapidly valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…BioID relies on the proximity of interacting proteins to the BirA* fusion, so assuring that the fusion protein is correctly localized is essential (Kim et al ., ). We titrated the expression level of the Ty1‐BirA*‐TOEFAZ1 fusion compared to a cell line where both endogenous TOEFAZ1 alleles had been tagged with 3×‐Ty1 (McAllaster et al ., ). We found that expression of the BirA*‐TOEFAZ1 fusion at 40 ng ml −1 of doxycycline was very similar to the double‐tagged endogenous levels of protein (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…BioID relies on the proximity of interacting proteins to the BirA* fusion, so assuring that the fusion protein is correctly localized is essential (Kim et al ., ). We titrated the expression level of the Ty1‐BirA*‐TOEFAZ1 fusion compared to a cell line where both endogenous TOEFAZ1 alleles had been tagged with 3×‐Ty1 (McAllaster et al ., ). We found that expression of the BirA*‐TOEFAZ1 fusion at 40 ng ml −1 of doxycycline was very similar to the double‐tagged endogenous levels of protein (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We included proteins that had been previously identified as TOEFAZ1 interactors but whose localizations were not reported (Zhou et al, 2016b). Each gene selected for analysis was initially N-terminally tagged at its endogenous locus with three copies of the Ty1 epitope using a Gibson Assembly TM strategy (McAllaster et al, 2016). Clonal cell lines for each protein were tested for correct insertion of the endogenous tag using PCR on isolated genomic DNA with primers specific for each locus and anti-Ty1 western blotting to test the size of the tagged protein.…”
Section: Optimized Toefaz1 Bioid Identifies Nearly 500 Proximal Neighmentioning
confidence: 99%
See 3 more Smart Citations